Natural and dynamical neutrino mass mechanism at the LHC - Gehrlein, Julia; Gonçalves, Dorival; Machado, Pedro A. N.; Perez-Gonzalez, Yuber F. [UNESP] (American Physical Society (APS), 2018)
We generalize the scalar triplet neutrino mass model, the type II seesaw. Our model displays compelling theoretical and experimental features. First, lepton number violation is dynamically generated, without introducing a naturalness problem, nor relying on arbitrarily small parameters. Second, we identify a smoking gun signature at the LHC that both probes the triplet structure of our seesaw mechanism and allows to disentangle it from the usual type II scenario. Additionally, we discuss other interesting phenomenological aspects of the model such as the presence of a massless Goldstone boson and deviations of standard model Higgs couplings.